2021
DOI: 10.54101/acen.2021.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic stroke and oral inflammatory diseases

Abstract: The aim of this study was to establish clinical significance of oral inflammatory diseases in ischaemic stroke (IS), how aware doctors and nurses are of this problem, and the safety and possibility of performing dental hygiene in patients with acute IS. Materials and methods. We examined 100 patients who had suffered an ischaemic stroke in the internal carotid artery territory within 6 to 48 hours. The efficacy of dental hygiene and the risk of developing chronic oral sepsis were evaluated using the Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…38 Studies in the 45-74 years old age group also reported that gender did not affect mortality or recovery of brain function at the end of the acute ischemic stroke period. 39 However, several studies showed that women experience higher mortality during ischemic stroke treatment in hospitals, 37,40 worse functional outcomes, 41 and worse locomotor function at 1 and 5 years of follow-up after ischemic stroke. 42 Differences in ischemic stroke outcomes based on gender are influenced by gene-related mechanisms, sexrelated steroid hormones, and social culture.…”
Section: Discussionmentioning
confidence: 99%
“…38 Studies in the 45-74 years old age group also reported that gender did not affect mortality or recovery of brain function at the end of the acute ischemic stroke period. 39 However, several studies showed that women experience higher mortality during ischemic stroke treatment in hospitals, 37,40 worse functional outcomes, 41 and worse locomotor function at 1 and 5 years of follow-up after ischemic stroke. 42 Differences in ischemic stroke outcomes based on gender are influenced by gene-related mechanisms, sexrelated steroid hormones, and social culture.…”
Section: Discussionmentioning
confidence: 99%